Kajian Etnomatematika : Eksplorasi Bangunan Masjid Jami’ Air Tiris Dalam Pembelajaran Geometri dan Pengukuran - alifia, shalsabila (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
The presence of Ethnomathematics is a link between culture and education, especially in mathematics learning. The purpose of this study is to describe the results of ethnomathematical exploration contained in the Jami' Air Tiris Mosque building on geometry and measurement concepts in mathematics learning. This research is qualitative research with an ethnographic approach. The data sources used in this study were obtained from observation, interview, and documentation data. The results of this study concluded that (1) There are several mathematical activities in the Architecture of Jami' Air Tiris Mosque, namely measuring activities, designing activities, and explaining activities. (2) The concept of geometry found in Masjid Jami' Air Tiris is the concept of building flat, building space, and the concept of geometric transformation. The design of Masjid Jami' Air Tiris uses standard measurement methods as well as non-standard measurements. The mathematical concepts contained in the Jami' Masjid can be used to introduce and understand the concepts of Geometry and Measurement through local culture.